2006
DOI: 10.1509/jmkr.43.3.420
|View full text |Cite
|
Sign up to set email alerts
|

Models for Heterogeneous Variable Selection

Abstract: Marketing managers are interested in knowing how consumers will react to different product configurations. The product manager can change physical attributes through the design of the product and the perception of psychological attributes through promotion strategies. Because consumers are heterogeneous in their tastes and preferences, aggregate level estimates of attribute importance are insufficient to describe the market. New research methods focus on obtaining individual level estimates of attribute import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 34 publications
1
49
1
Order By: Relevance
“…Although it is beneficial if such information is collected, constraints on survey size, or re-examination of prior datasets that did not ask such questions, may mean that it is not available. Several studies probabilistically allow for nonattendance without the need for self-reported indicators [3,10,13,21].…”
Section: Heterogeneity Skew and Attribute Non-attendancementioning
confidence: 99%
“…Although it is beneficial if such information is collected, constraints on survey size, or re-examination of prior datasets that did not ask such questions, may mean that it is not available. Several studies probabilistically allow for nonattendance without the need for self-reported indicators [3,10,13,21].…”
Section: Heterogeneity Skew and Attribute Non-attendancementioning
confidence: 99%
“…The posterior mean of γ i indicates the probability that a variable is significant in the model and is not zero. Gilbride et al (2006) propose an extension to George and McCulloch (1993) that allows variable selection to be present in models with heterogeneity, where different respondents are sensitive to different variables. The multivariate extension of the standard variable selection model is specified as:…”
Section: Selective Use Of Variablesmentioning
confidence: 99%
“…Significant gains have been made in each of the areas mentioned above, including models of heterogeneity (Allenby and Rossi 1999), models for endogenous variables (Manchanda et al 2004) and models of variable selection (Gilbride et al 2006). Since research cannot simultaneously address all issues at once, these gains typically come in one area while using other, less advanced components in other areas of the model.…”
Section: Introductionmentioning
confidence: 99%
“…Accounting for it tends to improve statistical fit of discrete choice models and allows analysts to run a sensitivity analysis of estimates of welfare measures to assumptions on attribute attendance. Some statistical models that endogenously account for the degree of serial AN-A have already been used successfully (Gilbride 2006, Rigby and Burton 2006, Scarpa et al 2009, Hess and Hensher 2009). However, the specific monitoring of choice task AN-A---as a form of intra-panel variation---is yet to be explored in the practice of environmental valuation, and it has only been minimally explored in other fields.…”
Section: Introductionmentioning
confidence: 99%